Creation of Local Council Development Areas in Southwestern Nigeria: A SWOT Analysis - Odewale, Ayotunde David; Taleat, Bisiriyu Abiodun; Ajayi, Olubusayo Ayooluwa (African Journal of Stability and Development (AJSD), 2018)
The study examines the nature and rationale behind the creation of Local Council Development Areas (LCDAs) by some states in Nigeria, especially in southwestern Nigeria. In this paper, critical consideration is given to understanding why the creation of more local governments has not influenced development. Ordinarily, it is expected that the more government is closer to the people, the more development ought to be to the grassroots. Yet, this has not always been the case. This can be traced to the fact that the creation of local governments in Nigeria has always been influenced by political considerations rather than developmental considerations. The methodology used for this paper is based on content analysis. The SWOT Analysis tool was used to describe the strengths, weaknesses, opportunities and threats facing local government creation and administration in Nigeria. The findings revealed the strengths, weaknesses, opportunities and threats that are likely to occur. The paper suggests that creation of local government should be more on viability that would lead to development at the grassroots rather than the political gains surrounding such creation